Pengaruh Opini Audit Dan Audit Delay Terhadap Harga Saham Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Ro’yal Aina; Kurnia Indah Sumunar (Jurnal Akuntan Publik, 2023)
This study aims to determine the effect of audit opinion and audit delay on stock prices with firm size as a moderating variable. This research is a quantitative research using secondary data from the financial statements of banking companies that have been listed on the Indonesia Stock Exchange for the period 2019 to 2022. The sample in this study was obtained using the probability sampling method, and 20 companies were obtained so that the sample used was 80 data. Data analysis in this study used SPSS software version 27. The results showed that audit opinion had no effect on stock prices, while audit delay had a significant negative effect on stock prices. On the other hand, company size can strengthen the negative effect of audit opinion on stock prices, but cannot strengthen or weaken the effect of audit delay on stock prices.